1995
DOI: 10.1152/jn.1995.74.4.1563
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous activity and frequency selectivity of acoustically responsive vestibular afferents in the cat

Abstract: 1. Recordings were made from single afferent fibers in the inferior vestibular nerve. Firing rates of a substantial portion of the afferents with irregular background activity increased in response to moderately intense tone bursts. 2. Spontaneous activity from acoustically responsive vestibular afferents was statistically analyzed and compared with data from a more widespread sampling of primary afferents in the cat's vestibulocochlear nerve. Acoustically responsive vestibular afferents had interspike interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 0 publications
3
36
0
4
Order By: Relevance
“…Other studies have shown that the inferior vestibular nerve of the cat containing the saccular afferents displays a tuning curve to auditory stimulation peaking at 500-1,000 Hz, the frequency most effective in causing the Tullio phenomenon in cats [30]. From a functional perspective, it is the sacculocollic projection that underlies the inhibitory potential that is measured in the cVEMP in the sternocleidomastoid muscle.…”
Section: Audiometric Findingsmentioning
confidence: 98%
“…Other studies have shown that the inferior vestibular nerve of the cat containing the saccular afferents displays a tuning curve to auditory stimulation peaking at 500-1,000 Hz, the frequency most effective in causing the Tullio phenomenon in cats [30]. From a functional perspective, it is the sacculocollic projection that underlies the inhibitory potential that is measured in the cVEMP in the sternocleidomastoid muscle.…”
Section: Audiometric Findingsmentioning
confidence: 98%
“…In addition to reporting linear acceleration, the otolith organs indicate head position by changes in activation as their orientations change relative to the gravity vector. In the mammalian literature, the utricle and saccule are often treated as similar, just oriented differently, but in at least some mammals, the saccule also detects moderately loud sounds at frequencies of 1 kHz and less (McCue and Guinan, 1994). In other animals, saccules can differ in being primarily auditory (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…La valoración de la función del sáculo y del utrículo ha sido objeto de intensa investigación básica y clínica [6][7][8][9][10][11] . Los potenciales evocados miogénicos vestibulares (VEMP) son ondas electromiográficas bifásicas de corta latencia evocadas principalmente por estímulos acústicos intensos.…”
Section: Artículos Originalesunclassified